Quasi-solid electrolyte, preparation method and application thereof, and button cell
By using a quasi-solid electrolyte crosslinked with cyclodextrin in lithium-ion batteries, the safety and mechanical performance deficiencies of liquid electrolytes have been addressed, resulting in lithium/sodium-ion batteries with high mechanical strength, high ionic conductivity, and good electrochemical stability.
Patent Information
- Application Number
- CN202310814572.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-07-04
AI Technical Summary
Existing lithium-ion battery liquid electrolytes have safety issues, are prone to thermal runaway due to exothermic reactions, and have insufficient mechanical properties.
The quasi-solid electrolyte with cyclodextrin crosslinking is formed by crosslinking cyclodextrin and inorganic pore-forming agents such as ZSM-5 molecular sieve in the polymer to form a porous complex, which enhances mechanical properties and reduces side reactions of electrolyte solvent.
It improves the mechanical strength and ionic conductivity of the electrolyte, enhances the electrode/electrolyte contact, and improves the initial charge/discharge capacity and cycle stability of lithium/sodium ion batteries.
Smart Images

Figure CN119275339A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a quasi-solid electrolyte, a preparation method and application thereof, and a button battery. Background Art
[0002] After conquering the market for portable electronic devices, lithium-ion batteries are now increasingly used in (hybrid) electric vehicles and static energy storage devices. For the large-scale application of lithium-ion batteries, a key issue is safety. Existing alkali metal batteries usually use liquid electrolytes composed of thermally unstable salts (such as hexafluorophosphates) and highly flammable organic solvents (such as carbonates and ethers). The root cause of battery safety issues is essentially due to a series of exothermic reactions, which lead to uncontrollable thermal runaway of the battery system. Semi-solid electrolytes, also known as gel electrolytes, can solve the problem of electrolyte leakage and enhance safety assurance. This semi-solid electrolyte not only maintains the excellent electrochemical properties of liquid electrolytes (such as high ionic conductivity and excellent electrode|electrolyte interface compatibility), but also has good mechanical properties (strength, flexibility, etc.), which is conducive to its application in the field of lithium-ion batteries.
[0003] The first gel electrolyte (based on poly(vinyl formal) / PVdF copolymer swollen with liquid organic carbonate), also known as quasi-solid electrolyte, semi-solid electrolyte or solid-liquid hybrid electrolyte, was reported by Feuillade and Perche in 1975. The basic idea is to develop a solid, mechanically stable, flexible and lightweight electrolyte by fixing the liquid electrolyte in the polymer host matrix through the formation of gel. The biggest advantage of semi-solid electrolyte is that it combines the beneficial properties of the polymer matrix (i.e. mechanical stability, flexibility, reduced leakage) with the excellent ionic conductivity of the liquid organic electrolyte by sharing the cohesion and diffusivity of the solid and liquid. In addition, the encapsulation of the liquid electrolyte in the solid polymer host matrix leads to enhanced electrode / electrolyte contact and interface. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a quasi-solid electrolyte cross-linked by cyclodextrin and a preparation method and application thereof. The quasi-solid electrolyte of the present invention is assembled into a quasi-solid-state lithium / sodium ion battery as a gel electrolyte, which has the advantages of high mechanical strength, good tensile properties, high ionic conductivity and good electrochemical stability window.
[0005] The present invention unexpectedly discovered through research that in the solution, the bond of cyclodextrin is dynamically changing, which does not affect ion migration while ensuring mechanical strength, and is an excellent performance for quasi-solid electrolytes. Cyclodextrin is a type of water-soluble molecule with a hollow cylindrical three-dimensional ring structure. The cyclodextrin ring is hydrophilic outside and inside the ring. The nitrile group of the nitrile polymer is hydrophobic, so in the aqueous solution, it tends to enter the interior of the cyclodextrin due to hydrophobic interactions. The addition of inorganic pore-forming agents, especially the present invention unexpectedly discovered that the use of molecular sieves such as ZSM-5 molecular sieves, in addition to enhancing the mechanical properties of the membrane, the pore size at the junction of the two pores of the molecular sieve is 0.9nm, so it can accommodate free electrolyte solvents, thereby reducing the side reactions of the electrolyte solvents. After drying and removing water, the membrane swells with an appropriate amount of alkali metal ion electrolyte to obtain a quasi-solid electrolyte membrane. The quasi-solid electrolyte membrane obtained by the present invention is assembled into a button battery with a lithium / sodium sheet, a lithium / sodium ion positive electrode sheet, a gasket and a spring, and the button battery has the advantages of high first charge and discharge capacity, good cycle stability and high coulomb efficiency.
[0006] According to a first aspect of the present invention, the present invention provides a quasi-solid electrolyte, which contains a cyclodextrin-crosslinked nitrile-containing polymer, an electrolyte solvent, and an inorganic pore former.
[0007] According to a second aspect of the present invention, the present invention provides a method for preparing a quasi-solid electrolyte, the preparation method comprising:
[0008] a) dissolving a nitrile-containing polymer in an organic solvent, and adding an inorganic pore-forming agent to obtain a first solution;
[0009] b) mixing cyclodextrin with water to form a second solution;
[0010] c) coating the first solution on the mold;
[0011] d) placing the mold coated with the first solution into the second solution, and obtaining a porous composite after removing water;
[0012] e) immersing the porous composite into an electrolyte to swell.
[0013] According to a third aspect of the present invention, the present invention provides use of the quasi-solid electrolyte described in the present invention or the quasi-solid electrolyte prepared by the method described in the present invention in a battery.
[0014] According to a fourth aspect of the present invention, the present invention provides a button-type battery, wherein the electrolyte of the button-type battery contains the quasi-solid electrolyte described in the present invention or the quasi-solid electrolyte prepared by the method described in the present invention.
[0015] The quasi-solid electrolyte of the invention has a tensile strength of 2-3 MPa, a tensile rate of 30-80%, an ion conductivity of 1-5 mS / cm, and is electrochemically stable within a voltage range of 1-4.6 V.
[0016] The quasi-solid electrolyte of the present invention is assembled into a quasi-solid-state lithium / sodium ion battery as a gel electrolyte, and has the advantages of high mechanical strength, good tensile properties, high ionic conductivity and a good electrochemical stability window. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a SEM image of the dynamically bonded quasi-solid electrolyte of Example 1;
[0018] Figure 2 This is a SEM image of the quasi-solid electrolyte without dynamic bonds in Comparative Example 1;
[0019] Figure 3 The first charge and discharge curve of the dynamically bonded quasi-solid electrolyte of Example 1;
[0020] Figure 4 This is the first charge and discharge curve of the quasi-solid electrolyte without dynamic bonding in Comparative Example 1;
[0021] Figure 5 The discharge capacity of the two samples of Example 1 and Comparative Example 1 after being activated at 0.1C and cycled at 0.5C for 100 cycles;
[0022] Figure 6 The cyclic coulombic efficiency of the two samples of Example 1 and Comparative Example 1 is compared, and the current density is 0.5C. DETAILED DESCRIPTION
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings commonly understood by those skilled in the art. In the event of a conflict, the definitions in this specification shall prevail.
[0025] In the context of this specification, any two or more aspects of the present invention may be arbitrarily combined, and the technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0026] Unless otherwise specified, percentages, parts, ratios, etc. mentioned in this specification are based on weight, unless the weight basis does not conform to the common understanding of those skilled in the art.
[0027] In the present invention, the quasi-solid electrolyte is also called a semi-solid electrolyte, a gel electrolyte, or a solid-liquid mixed electrolyte.
[0028] The invention provides a quasi-solid electrolyte, which contains a cyclodextrin cross-linked nitrile-containing polymer, an electrolyte and an inorganic pore-forming agent.
[0029] According to a preferred embodiment of the present invention, the tensile strength of the quasi-solid electrolyte is 2-3 MPa.
[0030] According to a preferred embodiment of the present invention, the elongation of the quasi-solid electrolyte is 30-80%, preferably 60-75%, for example, 60%, 65%, 70%, 71%, 72%, 73%, 74%, 75%.
[0031] According to a preferred embodiment of the present invention, the ionic conductivity of the quasi-solid electrolyte is 1-5mS / cm; for example, 1.2mS / cm, 1.4mS / cm, 1.6mS / cm, 1.8mS / cm, 2mS / cm, 2.2mS / cm, 2.4mS / cm, 2.6mS / cm, 2.8mS / cm, 3.0mS / cm, 3.2mS / cm, 3.4mS / cm, 3.6mS / cm, 3.8mS / cm, 4.0mS / cm, 4.2mS / cm, 4.4mS / cm, 4.6mS / cm, 4.8mS / cm; preferably 2-4.5mS / cm.
[0032] In the present invention, the amount of the inorganic pore former can be selected in a wide range. According to a preferred embodiment of the present invention, the mass ratio of the inorganic pore former to the nitrile-containing polymer is 0.5-5:1, preferably 1-1.5:1. The aforementioned preferred embodiment has the advantages of being difficult to be punctured and having high mechanical strength.
[0033] In the present invention, the amount of cyclodextrin can be selected in a wide range. According to a preferred embodiment of the present invention, the mass ratio of cyclodextrin to the nitrile-containing polymer is 0.1-1:1, preferably 0.3-0.6:1.
[0034] In the present invention, the mass ratio of the electrolyte to the nitrile-containing polymer is 0.11-0.67:1, preferably 0.25-0.43:1. The amount of 0.3:1 is used as an exemplary description in the embodiments, but the present invention is not limited thereto.
[0035] In the present invention, the optional range of nitrile-containing polymer types is relatively wide. For the present invention, according to a preferred embodiment of the present invention, the nitrile-containing polymer includes but is not limited to one or more of polyacrylonitrile, polybutenenitrile, poly(acrylonitrile-co-styrene), poly(butyl acrylate-co-acrylonitrile), preferably polyacrylonitrile; preferably, the nitrile-containing polymer is selected from one or more of molecular weights of 10W, 15W and 30W.
[0036] In the present invention, the cyclodextrin type can be selected from a wide range. For the present invention, the cyclodextrin is preferably selected from one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, preferably γ-cyclodextrin. The above preferred technical solution is used to prepare a quasi-solid electrolyte with the advantages of high tensile strength and large elongation.
[0037] In the present invention, the optional range of types of the inorganic pore-forming agent is relatively wide. For the present invention, the inorganic pore-forming agent preferably includes but is not limited to one or more of ZSM-5 molecular sieve, ZSM-11 molecular sieve, ZSM-34 molecular sieve, alumina (Al2O3), silicon dioxide (SiO2) and titanium dioxide (TiO2), preferably one or more selected from ZSM-5 molecular sieve, ZSM-11 molecular sieve and ZSM-34 molecular sieve; more preferably ZSM-5 molecular sieve.
[0038] According to a preferred embodiment of the present invention, preferably, the inorganic pore-forming agent is selected from a material having a silicon-aluminum ratio of 30-80 and a specific surface area of 400-500 m 2 / g of ZSM-5 molecular sieve.
[0039] In the present invention, the electrolyte has a wide range of selectable types, and all commonly used electrolytes can be used in the present invention. For the present invention, the concentration of the alkali metal salt in the electrolyte is preferably 0.5-1.2 mol / L.
[0040] In the present invention, the alkali metal salt has a wide range of optional types. For the present invention, the alkali metal salt includes but is not limited to one or more of lithium salt, sodium salt, potassium salt; for the present invention, it is preferably selected from lithium salt; more preferably, the lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoroformimide) (LiTFSI) and lithium perchlorate (LiClO4). The use of the above preferred technical solution for preparing a semi-solid electrolyte has the advantages of high ionic conductivity and a wide electrochemical stability window.
[0041] In the present invention, the electrolyte solvent is mainly used for swelling of the nitrile-containing polymer, and there is no special requirement for its type. For the present invention, the electrolyte solvent preferably includes but is not limited to one or more of dimethyl sulfoxide, N-methylpyrrolidone, ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC) and ethylene glycol dimethyl ether (DME).
[0042] According to a preferred embodiment of the present invention, the electrolyte solvent includes a first solvent and a second solvent, the first solvent is selected from one or more of dimethyl sulfoxide, N-methylpyrrolidone, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate and ethylene glycol dimethyl ether; the second solvent is selected from 4-trifluoromethylethylene carbonate.
[0043] According to a preferred embodiment of the present invention, preferably, the first solvent is a mixture of ethylene carbonate and diethyl carbonate, and the mass ratio of the two is 0.1-10:1.
[0044] According to a preferred embodiment of the present invention, preferably, based on the total weight of the electrolyte solvent, the content of the first solvent is 80-95% by weight, and the content of the second solvent is 5-20% by weight.
[0045] According to a preferred embodiment of the present invention, the concentration of the alkali metal salt in the electrolyte is 0.5-1.2 mol / L.
[0046] According to a preferred embodiment of the present invention, the present invention provides a method for preparing a quasi-solid electrolyte, the preparation method comprising:
[0047] a) dissolving a nitrile-containing polymer in an organic solvent, and adding an inorganic pore-forming agent to obtain a first solution;
[0048] b) mixing cyclodextrin with water to form a second solution;
[0049] c) coating the first solution on the mold;
[0050] d) placing the mold coated with the first solution into the second solution, and obtaining a porous composite after removing water;
[0051] e) immersing the porous composite into an electrolyte to swell. The quasi-solid electrolyte prepared by the above preferred technical solution has the advantages of high ion conductivity and wide electrochemical stability window.
[0052] According to a preferred embodiment of the present invention, preferably, the nitrile-containing polymer is dissolved in an organic solvent and then stirred and mixed for 12-36 hours.
[0053] According to a preferred embodiment of the present invention, preferably, after adding the inorganic pore-forming agent, stirring and mixing are performed for 12-36 hours.
[0054] According to a preferred embodiment of the present invention, preferably, the mold coated with the first solution is placed in the second solution and then kept for 10-60 minutes.
[0055] According to a preferred embodiment of the present invention, preferably, the preparation method comprises:
[0056] a) dissolving the nitrile-containing polymer in an organic solvent, stirring and mixing for 12-36 hours; adding an inorganic pore-forming agent, stirring and mixing for 12-36 hours, to obtain a first solution;
[0057] b) mixing cyclodextrin with water to form a second solution;
[0058] c) coating the first solution on the mold;
[0059] d) placing the mold coated with the first solution into the second solution, keeping it for 10-60 minutes, and forming a film after removing water;
[0060] e) immersing the porous composite into an electrolyte to swell.
[0061] In the present invention, there is no special requirement for the type of the mold. For the present invention, it is preferred that the mold is a common mold such as glass.
[0062] According to a preferred embodiment of the present invention, preferably, in the first solution, the concentration of the nitrile-containing polymer is 0.05-0.15 g / mL; the concentration of the inorganic pore-forming agent is 0.075-0.225 g / mL.
[0063] According to a preferred embodiment of the present invention, preferably, in the second solution, the concentration of cyclodextrin is 0.01-0.016 g / ml.
[0064] According to a preferred embodiment of the present invention, the concentration of the alkali metal salt in the electrolyte is 0.5-1.2 mol / L.
[0065] In the present invention, there are no special requirements for the dehydration steps and conditions, and a commonly used dehydration method can be used. According to a preferred embodiment of the present invention, the dehydration step includes: placing in a vacuum drying oven, vacuum heating and drying, the heating temperature is 80-120°C, the vacuum pressure is 2-3MPa, and the heating time is 36-72h.
[0066] According to a preferred embodiment of the present invention, the water removal step comprises: placing the taken out material in a glove box with a water concentration lower than 0.01 ppm for 7-14 days.
[0067] According to a preferred embodiment of the present invention, there is no special requirement for the coating method, and common coating methods can be used in the present invention. For the present invention, preferably, uniform coating is performed by scraping with a scraper with a thickness of 250-1000 μm.
[0068] According to a preferred embodiment of the present invention, preferably, the porous composite is immersed in an electrolyte to swell, and there is no special requirement for the swelling conditions. For the present invention, the preferred time is 5-90 minutes.
[0069] According to a preferred embodiment of the present invention, the present invention provides a method for preparing a cyclodextrin cross-linked quasi-solid electrolyte;
[0070] Preferably, the method comprises the following steps:
[0071] A) dissolving polyacrylonitrile in an organic solvent and stirring at room temperature until completely dissolved;
[0072] Preferably, the polyacrylonitrile is a mixture of one or more of molecular weights of 10W, 15W and 30W;
[0073] Preferably, the organic solvent is dimethyl sulfoxide;
[0074] B) After polyacrylonitrile is dissolved, an inorganic pore-forming agent is added thereto and stirred at room temperature;
[0075] Preferably, the inorganic pore-forming agent is selected from a material with a silicon-aluminum ratio of 30-80, a junction of the two pores of 0.9 nm, and a specific surface area of 400-500 m 2 / g ZSM-5 molecular sieve;
[0076] Preferably, the stirring time is 12-24h;
[0077] C) Dissolve cyclodextrin in deionized water and stir until completely dissolved to obtain a cyclodextrin solution:
[0078] Preferably, the type of cyclodextrin is one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin;
[0079] D) uniformly coating the solution in A) on a flat glass, and then placing the flat glass in the cyclodextrin solution in C), allowing the solution to exchange for a period of time, placing the membrane in a vacuum drying oven to dry, and immersing it in an electrolyte to swell;
[0080] According to a preferred embodiment of the present invention, preferably, the uniform coating is performed by scraping with a scraper having a thickness of 250-1000 μm.
[0081] According to a preferred embodiment of the present invention, preferably, the exchange time in the solution is 30-90 min.
[0082] According to a preferred embodiment of the present invention, preferably, the drying temperature of the vacuum drying is 80-120° C., and the heating time is 36-60 h.
[0083] E) Assembling the three-layer porous solid electrolyte membrane described in D) with a lithium / sodium sheet, a lithium / sodium ion positive electrode sheet, a gasket and a spring into a button cell.
[0084] The present invention provides the use of the quasi-solid electrolyte of the present invention or the quasi-solid electrolyte prepared by the method of the present invention in a battery. The quasi-solid electrolyte of the present invention has the advantages of good contact with electrodes and high ion conductivity when applied to batteries.
[0085] The present invention provides a button-type battery, wherein the electrolyte of the button-type battery contains the quasi-solid electrolyte of the present invention. The button-type battery obtained by using the electrolyte of the present invention has the advantages of high initial discharge capacity and high coulombic efficiency.
[0086] For ease of understanding of the present invention, the present invention enumerates embodiment as follows. But those skilled in the art should understand that the embodiment is only to help understand the present invention, should not be regarded as specific limitation of the present invention. The endpoints and any value of the range disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood to include values close to these ranges or values.
[0087] Example 1
[0088] 1. Preparation method of quasi-solid electrolyte containing dynamic cross-linking bonds
[0089] 2 g of polyacrylonitrile with a molecular weight of 15 W was dissolved in 18 mL of dimethyl sulfoxide and stirred magnetically at room temperature for 12 h to obtain a polyacrylonitrile solution. 3 g of a silicon-aluminum ratio of 45 and a specific surface area of 450 m 2 / g ZSM-5, stirred for 24h.
[0090] Take 1g of γ-cyclodextrin and add it to 99ml of deionized water, stir until it is completely dissolved, and then pour it into a clean flat tray.
[0091] Take the above solution, apply it evenly on the flat glass with a 1000μm scraper, slowly put it into the tray containing the cyclodextrin solution, let the solvent replace, keep it for 45min, and after the film is formed, put it into a vacuum oven and heat it at 100℃ for 48h to obtain a dry porous film. The porous film is characterized by X-ray diffractometer (XRD) and scanning electron microscope (SEM) for its crystallization properties and microstructure. The strength and elongation at break are tested by a tensile machine at a stretching speed of 100mm / min. After the porous membrane is placed in the lithium ion electrolyte and swelled for 5min, it is punched into the required size to obtain a quasi-solid electrolyte. The composition of the lithium ion electrolyte is 1mol / L LiPF6 dissolved in ethylene carbonate EC / diethyl carbonate DEC / 4-trifluoromethyl ethylene carbonate (EC / DEC / 4-trifluoromethyl ethylene carbonate mass ratio: 4.5:4.5:1), and the mass ratio of the electrolyte to the nitrile-containing polymer is 0.3:1.
[0092] 2. Assembly and testing of quasi-solid-state lithium-ion batteries
[0093] The above-mentioned synthetic porous semi-solid electrolyte was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet, a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1), a gasket and a spring. The obtained battery was tested for capacity (charge and discharge current of 0.1C) and cycle stability (charge and discharge current of 0.5C) by constant current charge and discharge. The semi-solid electrolyte was assembled into a 2035 button cell with a lithium sheet, a stainless steel sheet and a spring, and its electrochemical stability window was tested by linear sweep voltammetry with a scan rate of 1mV s -1 The conductivity was tested by electrochemical impedance spectroscopy at a frequency of 0.01-10 5 Hz.
[0094] Figure 1 This is a SEM image of the dynamically bonded quasi-solid electrolyte of Example 1, which shows that the material voids are evenly distributed, the microscopic morphology is dense, and the inorganic particles are evenly distributed, which is conducive to preventing dendrites from piercing;
[0095] Figure 2 This is a SEM image of the quasi-solid electrolyte without dynamic bonds in comparative example 1, which shows that the material morphology is relatively loose and has many pore structures, which is not conducive to preventing dendrites from piercing;
[0096] Figure 3 The first charge and discharge curve of the dynamically bonded quasi-solid electrolyte in Example 1, the current density is 0.1C, and the first discharge capacity is as high as 174 mAh g -1 , which is greatly improved compared with the control sample;
[0097] Figure 4 This is the first charge and discharge curve of the quasi-solid electrolyte without dynamic bonding in comparative example 1. The first discharge capacity is 165 mAh g-1 ;
[0098] Figure 5 The discharge capacity of the two samples of Example 1 and Comparative Example 1 after being activated at 0.1C and cycled at 0.5C for 100 cycles indicates that the cyclodextrin cross-linked polynitrile greatly improves the electrochemical stability window of the uncross-linked gel polymer;
[0099] Figure 6 The cyclic coulombic efficiency of the two samples of Example 1 and Comparative Example 1 is compared, and the current density is 0.5C. It can be seen from the figure that the coulombic efficiency of Example 1 is significantly improved, indicating that the battery in Example 1 has better reversibility and less electrolyte decomposition.
[0100] Example 2
[0101] 1. Preparation method of quasi-solid electrolyte containing dynamic cross-linking bonds
[0102] 2 g of polyacrylonitrile with a molecular weight of 15 W was dissolved in 18 mL of dimethyl sulfoxide and stirred magnetically at room temperature for 12 h to obtain a polyacrylonitrile solution. 3 g of a silicon-aluminum ratio of 45 and a specific surface area of 450 m 2 / g ZSM-5, stirred for 24h.
[0103] Take 1g of α-cyclodextrin and add it to 99ml of deionized water, stir until it is completely dissolved, and then pour it into a clean flat tray.
[0104] Take the above solution, apply it evenly on the flat glass with a 1000μm scraper, slowly put it into the tray containing the cyclodextrin solution, let the solvent replace, keep it for 45min, after the film is formed, put it into a vacuum oven, heat it at 100℃ for 48h, and get a dry porous film. Use a stretching machine to test its strength and elongation at break, and the stretching speed is 100mm / min. After the porous membrane is placed in the lithium ion electrolyte and swells for 5min, it is punched into the required size to obtain a quasi-solid electrolyte. The composition of the lithium ion electrolyte is 1mol / L LiPF6 dissolved in EC / DEC / 4-trifluoromethylethylene carbonate (4.5:4.5:1), and the mass ratio of the electrolyte to the nitrile-containing polymer is 0.3:1.
[0105] 2. Assembly and testing of quasi-solid-state lithium-ion batteries
[0106] The above-mentioned synthetic porous semi-solid electrolyte was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet, a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1), a gasket and a spring. The obtained battery was charged and discharged with a constant current to test its capacity (the charge and discharge current was 0.1C). The semi-solid electrolyte was assembled into a 2035 button cell with a lithium sheet, a stainless steel sheet and a spring, and its electrochemical stability window was tested by linear sweep voltammetry with a scan rate of 1mV s -1 The conductivity was tested by electrochemical impedance spectroscopy at a frequency of 0.01-10 5 Hz.
[0107] Example 3
[0108] 1. Preparation method of quasi-solid electrolyte containing dynamic cross-linking bonds
[0109] 2.0 g of polybutenenitrile with a molecular weight of 15 W was dissolved in 18 mL of dimethyl sulfoxide and stirred magnetically at room temperature for 12 h to obtain a polybutenenitrile solution. 3 g of a silicon-aluminum ratio of 45 and a specific surface area of 450 m 2 / g ZSM-5, stirred for 24h.
[0110] Take 1g of γ-cyclodextrin and add it to 99ml of deionized water, stir until it is completely dissolved, and then pour it into a clean flat tray.
[0111] Take the above solution, apply it evenly on the flat glass with a 1000μm scraper, slowly put it into the tray containing the cyclodextrin solution, let the solvent replace, keep it for 45min, after the film is formed, put it into a vacuum oven, heat it at 100℃ for 48h, and get a dry porous film. Use a stretching machine to test its strength and elongation at break, and the stretching speed is 100mm / min. After the porous membrane is placed in the lithium ion electrolyte and swells for 5min, it is punched into the required size to obtain a quasi-solid electrolyte. The composition of the lithium ion electrolyte is 1mol / L LiPF6 dissolved in EC / DMC / 4-trifluoromethylethylene carbonate (4.5:4.5:1), and the mass ratio of the electrolyte to the nitrile-containing polymer is 0.3:1.
[0112] 2. Assembly and testing of quasi-solid-state lithium-ion batteries
[0113] The above-mentioned synthetic porous semi-solid electrolyte was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet, a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1), a gasket and a spring. The obtained battery was charged and discharged with a constant current to test its capacity (the charge and discharge current was 0.1C). The semi-solid electrolyte was assembled into a 2035 button cell with a lithium sheet, a stainless steel sheet and a spring, and its electrochemical stability window was tested by linear sweep voltammetry with a scan rate of 1mV s -1The conductivity was tested by electrochemical impedance spectroscopy at a frequency of 0.01-10 5 Hz.
[0114] Example 4
[0115] 1. Preparation method of quasi-solid electrolyte containing dynamic cross-linking bonds
[0116] 2 g of polyacrylonitrile with a molecular weight of 15 W was dissolved in 18 mL of dimethyl sulfoxide, and magnetically stirred at room temperature for 12 h to obtain a polyacrylonitrile solution. 3 g of silica was added and stirred for 24 h.
[0117] Take 1g of γ-cyclodextrin and add it to 99ml of deionized water, stir until it is completely dissolved, and then pour it into a clean flat tray.
[0118] Take the above solution, apply it evenly on the flat glass with a 1000μm scraper, slowly put it into the tray containing the cyclodextrin solution, let the solvent replace, keep it for 45min, after the film is formed, put it into a vacuum oven, heat it at 100℃ for 48h, and get a dry porous film. Use a stretching machine to test its strength and elongation at break, and the stretching speed is 100mm / min. After the porous membrane is placed in the lithium ion electrolyte and swells for 5min, it is punched into the required size to obtain a quasi-solid electrolyte. The composition of the lithium ion electrolyte is 1mol / L NaPF6 dissolved in EC / DMC / 4-trifluoromethylethylene carbonate (4.5:4.5:1), and the mass ratio of the electrolyte to the nitrile-containing polymer is 0.3:1.
[0119] 2. Assembly and testing of quasi-solid-state lithium-ion batteries
[0120] The above-mentioned synthetic porous semi-solid electrolyte was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet, a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1), a gasket and a spring. The obtained battery was charged and discharged with a constant current to test its capacity (the charge and discharge current was 0.1C). The semi-solid electrolyte was assembled into a 2035 button cell with a lithium sheet, a stainless steel sheet and a spring, and its electrochemical stability window was tested by linear sweep voltammetry with a scan rate of 1mV s -1 The conductivity was tested by electrochemical impedance spectroscopy at a frequency of 0.01-10 5 Hz.
[0121] Example 5
[0122] 1. Preparation method of quasi-solid electrolyte containing dynamic cross-linking bonds
[0123] 2 g of polyacrylonitrile with a molecular weight of 15 W was dissolved in 18 mL of dimethyl sulfoxide and stirred magnetically at room temperature for 12 h to obtain a polyacrylonitrile solution. 3 g of a silicon-aluminum ratio of 45 and a specific surface area of 450 m 2 / g ZSM-5, stir for 24h. Take 1g of γ-cyclodextrin and add it to 99ml of deionized water, stir until it is completely dissolved, and then pour it into a clean flat tray.
[0124] Take the above solution and evenly apply it on a flat glass with a 1000μm scraper, then slowly put it into the tray containing the cyclodextrin solution to allow the solvent to be replaced and keep it for 45 minutes. After the film is formed, put it into a vacuum oven and heat it at 100℃ for 48 hours to obtain a dry porous film. Use a stretching machine to test its strength and elongation at break at a stretching speed of 100mm / min. After the porous membrane is placed in a lithium ion electrolyte and swelled for 5 minutes, it is punched into the required size to obtain a quasi-solid electrolyte. The composition of the lithium ion electrolyte is 1mol l -1 LiPF6 was dissolved in EC / DEC (1:1), and the mass ratio of electrolyte to nitrile-containing polymer was 0.3:1.
[0125] 2. Assembly and testing of quasi-solid-state lithium-ion batteries
[0126] The above-mentioned synthetic porous semi-solid electrolyte was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet, a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1), a gasket and a spring. The obtained battery was charged and discharged with a constant current to test its capacity (the charge and discharge current was 0.1C). The semi-solid electrolyte was assembled into a 2035 button cell with a lithium sheet, a stainless steel sheet and a spring, and its electrochemical stability window was tested by linear sweep voltammetry with a scan rate of 1mV s -1 The conductivity was tested by electrochemical impedance spectroscopy at a frequency of 0.01-10 5 Hz.
[0127] Example 6
[0128] 1. Preparation method of quasi-solid electrolyte containing dynamic cross-linking bonds
[0129] 2 g of polyacrylonitrile with a molecular weight of 15 W was dissolved in 18 mL of dimethyl sulfoxide and stirred magnetically at room temperature for 12 h to obtain a polyacrylonitrile solution. 3 g of polyacrylonitrile with a silicon-aluminum ratio of 45 and a specific surface area of 450 m 2 / g ZSM-5, stirred for 24h.
[0130] Take 1g of γ-cyclodextrin and add it to 99ml of deionized water, stir until it is completely dissolved, and then pour it into a clean flat tray.
[0131] Take the above solution and evenly apply it on a flat glass with a 1000μm scraper, then slowly put it into the tray containing the cyclodextrin solution to allow the solvent to be replaced and keep it for 45 minutes. After the film is formed, put it into a vacuum oven and heat it at 60℃ for 48 hours to obtain a dry porous film. Use a stretching machine to test its strength and elongation at break, and the stretching speed is 100mm / min. After the porous membrane is placed in a lithium ion electrolyte and swells for 5 minutes, it is punched into the required size to obtain a quasi-solid electrolyte. The composition of the lithium ion electrolyte is 0.8mol l -1 LiPF6 was dissolved in EC / DEC / 4-trifluoromethylethylene carbonate (4.5:4.5:1), and the mass ratio of the electrolyte to the nitrile-containing polymer was 0.3:1.
[0132] 2. Assembly and testing of quasi-solid-state lithium-ion batteries
[0133] The above-mentioned synthetic porous semi-solid electrolyte was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet, a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1), a gasket and a spring. The obtained battery was charged and discharged with a constant current to test its capacity (the charge and discharge current was 0.1C). The semi-solid electrolyte was assembled into a 2035 button cell with a lithium sheet, a stainless steel sheet and a spring, and its electrochemical stability window was tested by linear sweep voltammetry with a scan rate of 1mV s -1 The conductivity was tested by electrochemical impedance spectroscopy at a frequency of 0.01-10 5 Hz.
[0134] Comparative Example 1
[0135] 1. Synthesis of quasi-solid electrolytes without dynamic cross-linking bonds
[0136] 2 g of polyacrylonitrile with a molecular weight of 15 W was dissolved in 20 mL of dimethyl sulfoxide and stirred magnetically at room temperature for 12 h to obtain a polyacrylonitrile solution. 3 g of ZSM-5m with a silicon-aluminum ratio of 45 and a specific surface area of 450 was added. 2 / g, stirred for 24h.
[0137] Take the above solution, apply it evenly on a flat glass with a 1000μm scraper, slowly put it into a tray filled with deionized water, let the solvent replace, keep it for 45min, and after the film is formed, put it into a vacuum oven and heat it at 100℃ for 48h to obtain a dry porous film. The porous film is characterized by X-ray diffractometer (XRD) and scanning electron microscope (SEM) for its crystallization properties and microstructure. The strength and elongation at break are tested by a tensile machine at a stretching speed of 100mm / min. After the porous membrane is placed in a lithium ion electrolyte and swelled for 5min, it is punched into the required size to obtain a quasi-solid electrolyte. The composition of the lithium ion electrolyte is 1mol / L LiPF6 dissolved in EC / DEC / 4-trifluoromethylethylene carbonate (4.5:4.5:1), and the mass ratio of the electrolyte to the nitrile-containing polymer is 0.3:1.
[0138] 2. Assembly and testing of all-solid-state lithium-ion batteries
[0139] The above-mentioned synthetic porous electrolyte membrane was used as an electrolyte and assembled into a 2035 button cell with a lithium sheet, a lithium iron phosphate positive electrode sheet (lithium iron phosphate: polyvinylidene fluoride: acetylene black = 8:1:1), a gasket and a spring. The obtained battery was tested for capacity (charge and discharge current of 0.1C) and cycle stability (charge and discharge current of 0.5C) by constant current charge and discharge. The semi-solid electrolyte was assembled into a 2035 button cell with a lithium sheet, a stainless steel sheet and a spring, and its electrochemical stability window was tested by linear sweep voltammetry with a scan rate of 1mV s -1 The conductivity was tested by electrochemical impedance spectroscopy at a frequency of 0.01-10 5 Hz.
[0140] Table 1
[0141]
[0142] The embodiments of the present invention are only used to illustrate the detailed process of the present invention, but the present invention is not limited to the above detailed process, that is, the present invention can be implemented without relying on the steps described in the above embodiments. In summary, any improvements made by those skilled in the art to the present invention, including replacement of the raw materials and additives described in the present invention, selection of specific implementation methods, etc., all belong to the protection scope and disclosure scope of the present invention.
[0143] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A quasi-solid electrolyte, characterized in that: The electrolyte contains a cyclodextrin cross-linked nitrile-containing polymer, an electrolyte and an inorganic pore-forming agent.
2. The quasi-solid electrolyte according to claim 1, wherein: The tensile strength of the quasi-solid electrolyte is 2-3 MPa; and / or The stretchability of the quasi-solid electrolyte is 30-80%, preferably 60-75%; and / or The ionic conductivity of the quasi-solid electrolyte is 1-5 mS / cm, preferably 2-4.5 mS / cm; and / or The mass ratio of cyclodextrin to nitrile-containing polymer is 0.1-1:1, preferably 0.3-0.6:1; and / or The mass ratio of the inorganic pore former to the nitrile-containing polymer is 0.5-5:1, preferably 1-1.5:1; and / or The mass ratio of the electrolyte to the nitrile-containing polymer is 0.11-0.67:1, preferably 0.25-0.43:
1.
3. The quasi-solid electrolyte according to claim 1 or 2, wherein: The nitrile-containing polymer is selected from one or more of polyacrylonitrile, polybutenenitrile, poly(acrylonitrile-co-styrene), poly(butyl acrylate-co-acrylonitrile) and poly(ethylene oxide-co-acrylonitrile), preferably polyacrylonitrile; Preferably, the nitrile-containing polymer is selected from one or more of the molecular weights of 10W, 15W and 30W; and / or The cyclodextrin is selected from one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, preferably γ-cyclodextrin; and / or The inorganic pore-forming agent is selected from one or more of ZSM-5 molecular sieve, ZSM-11 molecular sieve, ZSM-34 molecular sieve, alumina, silicon dioxide and titanium dioxide, preferably one or more of ZSM-5 molecular sieve, ZSM-11 molecular sieve and ZSM-34 molecular sieve; more preferably ZSM-5 molecular sieve; Preferably, the inorganic pore-forming agent is selected from a material having a silicon-to-aluminum ratio of 30-80 and a specific surface area of 400-500 m 2 / g ZSM-5 molecular sieve; and / or In the electrolyte, the concentration of the alkali metal salt is 0.5-1.2 mol / L; Preferably, The alkali metal salt is selected from one or more of lithium salts, sodium salts and potassium salts; preferably selected from lithium salts; more preferably, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoroformimide) and lithium perchlorate; and / or The electrolyte solvent is selected from one or more of dimethyl sulfoxide, N-methylpyrrolidone, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate and ethylene glycol dimethyl ether; Preferably, The electrolyte solvent includes a first solvent and a second solvent, wherein the first solvent is selected from one or more of dimethyl sulfoxide, N-methylpyrrolidone, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate and ethylene glycol dimethyl ether; and the second solvent is selected from 4-trifluoromethylethylene carbonate; Preferably, the first solvent is a mixture of ethylene carbonate and diethyl carbonate, and the mass ratio of the two is 0.1-10:1; Preferably, based on the total weight of the electrolyte solvent, the content of the first solvent is 80-95% by weight, and the content of the second solvent is 5-20% by weight.
4. A method for preparing a quasi-solid electrolyte, characterized in that: The preparation method comprises: a) dissolving a nitrile-containing polymer in an organic solvent, and adding an inorganic pore-forming agent to obtain a first solution; b) mixing cyclodextrin with water to form a second solution; c) coating the first solution on the mold; d) placing the mold coated with the first solution into the second solution, and obtaining a porous composite after removing water; e) immersing the porous composite into an electrolyte to swell.
5. The preparation method according to claim 4, wherein: The preparation method comprises: a) dissolving the nitrile-containing polymer in an organic solvent, stirring and mixing for 12-36 hours; adding an inorganic pore-forming agent, stirring and mixing for 12-36 hours, to obtain a first solution; b) mixing cyclodextrin with water to form a second solution; c) coating the first solution on the mold; d) placing the mold coated with the first solution into the second solution, keeping it for 10-60 minutes, and forming a film after removing water; e) immersing the porous composite into an electrolyte to swell.
6. The preparation method according to claim 4 or 5, wherein: The nitrile-containing polymer is selected from one or more of polyacrylonitrile, polybutenenitrile, poly(acrylonitrile-co-styrene), poly(butyl acrylate-co-acrylonitrile) and poly(ethylene oxide-co-acrylonitrile), preferably the nitrile-containing polymer is selected from one or more polyacrylonitrile with a molecular weight of 10W, 15W and 30W; and / or The cyclodextrin is selected from one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin; and / or The inorganic pore-forming agent is selected from one or more of ZSM-5 molecular sieve, ZSM-11 molecular sieve, ZSM-34 molecular sieve, alumina, silicon dioxide and titanium dioxide; Preferably, the inorganic pore-forming agent is selected from a material having a silicon-to-aluminum ratio of 30-80 and a specific surface area of 400-500 m 2 / g ZSM-5 molecular sieve; and / or The organic solvent is selected from dimethyl sulfoxide and / or N-methylpyrrolidone; and / or In the electrolyte, the concentration of the alkali metal salt is 0.5-1.2 mol / L; Preferably, The alkali metal salt is selected from one or more of lithium salts, sodium salts and potassium salts; preferably selected from lithium salts; more preferably, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoroformimide) and lithium perchlorate; and / or The electrolyte solvent is selected from one or more of dimethyl sulfoxide, N-methylpyrrolidone, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate and ethylene glycol dimethyl ether; Preferably, The electrolyte solvent includes a first solvent and a second solvent, wherein the first solvent is selected from one or more of dimethyl sulfoxide, N-methylpyrrolidone, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate and ethylene glycol dimethyl ether; and the second solvent is selected from 4-trifluoromethylethylene carbonate; Preferably, the first solvent is a mixture of ethylene carbonate and diethyl carbonate, and the mass ratio of the two is 0.1-10:1; Preferably, based on the total weight of the electrolyte solvent, the content of the first solvent is 80-95% by weight, and the content of the second solvent is 5-20% by weight.
7. The preparation method according to any one of claims 4 to 6, wherein: In the first solution, the concentration of the nitrile-containing polymer is 0.05-0.15 g / mL; the concentration of the inorganic pore-forming agent is 0.075-0.225 g / mL; and / or In the second solution, the concentration of cyclodextrin is 0.01-0.016 g / ml.
8. The preparation method according to any one of claims 4 to 7, wherein: The dehydration step includes: placing in a vacuum drying oven, vacuum heating and drying, the heating temperature is 80-120° C., and the heating time is 36-72 hours.
9. Use of the quasi-solid electrolyte described in any one of claims 1 to 3 or the quasi-solid electrolyte prepared by the method described in any one of claims 4 to 8 in a battery.
10. A button battery, characterized in that: The electrolyte of the button cell contains the quasi-solid electrolyte described in any one of claims 1 to 3 or the quasi-solid electrolyte prepared by the method described in any one of claims 4 to 8.
Citation Information
Patent Citations
Microgel based on cyclodextrins and preparation method thereof
CN101665576A
Solid-state lithium ion battery and preparation method thereof
CN113130895A
Inorganic-organic composite electrolyte membrane, and preparation method and application thereof
CN113675460A
Energy storage device with polymer electrolyte and filler
CN114846666A
Microporous solid electrolytes and methods for preparing them
CN1331848A